Leishmania spp. in equids and their potential vectors in endemic areas of canine leishmaniasis - Carbonara, Mariaelisa; Mendoza-Roldan, Jairo Alfonso; Bezerra-Santos, Marcos Antônio; de Abreu Teles, Pedro Paulo; Lia, Riccardo Paolo; Locantore, Francesco; Iatta, Roberta; Volf, Petr; Otranto, Domenico (PLoS neglected tropical diseases, 2024)
Equids may be infected by zoonotic Leishmania spp., including Leishmania infantum, in regions where canine leishmaniasis (CanL) is endemic, and Leishmania martiniquensis, which has been reported in horses from Central Europe. This study was designed to evaluate the occurrence of both Leishmania spp. among equids living in CanL endemic areas of Italy, as well as to identify dipteran vectors from the same habitats. From March to October 2023, blood, serum and tissue samples from skin lesions were collected from equids (n = 98; n = 56 donkeys and n = 42 horses) living in Italy, as well as sand flies and biting midges. Blood samples (n = 98) and skin lesions (n = 56) were tested for Leishmania spp. by conventional and real time PCRs and sera were tested by immunofluorescence antibody tests (IFAT) for both L. infantum and L. martiniquensis. Insects were morphologically identified, and female specimens (n = 268 sand flies, n = 7 biting midges) analyzed for Leishmania DNA, as well as engorged sand flies (n = 16) for blood-meal detection. Two animals with skin lesions (i.e., one donkey and one horse) scored positive for Leishmania spp. DNA, and 19 animals (i.e., 19.4%; n = 13 donkeys and n = 6 horses) were seropositive for L. infantum, with five of them also for L. martiniquensis. Most seropositive animals had no dermatological lesions (i.e., 68.4%) while both animals molecularly positive for Leishmania spp. scored seronegative. Of the 356 sand flies collected, 12 females (i.e., n = 8 Sergentomyia minuta; n = 3 Phlebotomus perniciosus, n = 1 Phlebotomus perfiliewi) were positive for Leishmania spp. DNA, and one out of seven biting midges collected was DNA-positive for L. infantum. Moreover, engorged sand flies scored positive for human and equine DNA. Data suggest that equids living in CanL endemic areas are exposed to Leishmania spp., but their role in the circulation of the parasite needs further investigations.
Keywords: Endemic Diseases; Horses; Equidae; nemoci koní; Leishmania; Itálie; nemoci psů; leishmanióza; Female; psi; hmyz - vektory; Leishmaniasis; endemické nemoci; Leishmania infantum; mužské pohlaví; Insect Vectors; zvířata; koně; Ceratopogonidae; ženské pohlaví; Dogs; Animals; Male; Horse Diseases; Italy; Psychodidae; Dog Diseases